1988
DOI: 10.1016/0020-7292(88)90270-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence in middle‐aged women

Abstract: An anonymous questionnaire was used to interview 946 premenopausal women (age 29-52 years), previously either hysterectomized or laparoscopically sterilized, concerning disorders of the urinary tract. Of the 750 (79.3%) women that responded, 307 (40.9%) admitted to some degree of urinary disorder. The prevalence of urinary disorders was 170/415 (40.9%) for the women with a previous supravaginal or total hysterectomy and 137/335 (40.8%) for the women in the sterilization group. Of the responding women 85 (11.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 3 publications
1
40
2
Order By: Relevance
“…Calculation of the sample size was based on information on the prevalence of the primary outcome (urinary incontinence) among hysterectomised women -approximately 23% 5,16 . The calculation had a power of 0.80 to detect a significant difference of 5% (two-sided).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of the sample size was based on information on the prevalence of the primary outcome (urinary incontinence) among hysterectomised women -approximately 23% 5,16 . The calculation had a power of 0.80 to detect a significant difference of 5% (two-sided).…”
Section: Methodsmentioning
confidence: 99%
“…Total abdominal hysterectomy and subtotal abdominal hysterectomy have been compared in observational studies 8,14,16 . Despite the superiority of the randomised clinical trial in the evaluation of the treatment effects 17 , only two randomised clinical trials have been published 11,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding urinary frequency, nocturia and incontinence, a systematic review on urinary function following subtotal abdominal hysterectomy and total abdominal hysterectomy identified five observational studies, three of which, in addition to one randomized, controlled trial showed an increased risk of incontinence after total abdominal hysterectomy (22,(25)(26)(27). The remaining two, in addition to one randomized controlled trial showed no difference (20,28,29).…”
Section: Anaesthesia-related Complicationsmentioning
confidence: 99%
“…Stress urinary incontinence (SUI) is a widespread problem estimated to affect over 26% of middle-aged women in America and it induces social, sanitary, and psychological problems related to the patients' quality of life (1). Recently, considerable progress has been made toward treatments of SUI stemming from advances in understanding the pathogenesis (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%